Consumption of nitrogen by cultivares of sugar in Tabasco, Mexico - Salgado García, Sergio; Izquierdo Hernández, José; Lagunes Espinoza, Luz del Carmen; Palma López, David Jesús; Córdova Sanchez, Samuel; Ortiz Laurel, Hipólito; Castelán Estrada, Mepivoseth (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2017)
Efficiency in taking nitrogen sugarcane cultivars is not directly related yields stems per hectare. The objectives were to determine the effect of nitrogen fertilization on juice quality, performance, nitrogen demand and profitability. The study was conducted in the sugar factory Azsuremex (Tenosique, Tabasco) during the 2014/2015 cycle plant cane, under culture conditions without supplemental irrigation on soil Cambisol haplico. N rates were evaluated: 0, 120 and 180 kg ha-1 in 10 sugarcane cultivars. The results show that high doses of N adversely affected the quality of the juice. A positive linear response on performance, except MEX 69-290 cultivar presented the highest performance 120 kg.N.ha-1 was observed. N consumption was different between cultivars and increased as the dose of N. The internal efficiency index (EI) of nitrogen utilization ranged from 1.6 to 2.0 kg N per tons stem increased. In five of the evaluated cultivars is profitable fertilize with doses of 120 and/or 160 kg ha-1 of N.